Postpartum Women's Perceptions and Help-Seeking Behaviors Regarding Pregnancy/Childbirth's Impact on Sexual Function. (1st August 2022) - Kelley, E; Kingsberg, S; Pope, R
ABSTRACT: Introduction: Previous research indicates decreased sexual functioning in the postpartum period. Less research has examined women's perceptions of these changes and their help-seeking behaviors. Objective: This survey examined postpartum women's perspectives of the impact of pregnancy/childbirth on their sexual function and help-seeking behaviors. Methods: This was an observational, mixed-method online survey using Qualtrics platform. Participants were U.S. adult women who delivered in the previous three years. Results: A total of N = 573 primi- or multi-parous women completed surveys assessing changes in sexual function postpartum, help-seeking behaviors, and the Sexual Function Questionnaire-Medical Impact Scale (SFQ-MIS). Most (n = 482; 84.12%) identified as White and 550 women (95.99%) completed high school or higher education. Results indicated that 64.0% (n = 367) reported decreased desire, 55.63% (n=316) decreased arousal, and 7.94% (n = 45) anorgasmia. Further, 34.28% (n = 194) reported increased vaginal/vulvar/pelvic pain postpartum. On average, women were moderately adjusted to postpartum changes in their sex life (Mean SFQ-MIS score = 6.65, SD = 0.10, range = 0 -10).Most women with decreased desire or arousal, anorgasmia, or increased pain postpartum did not seek help either from informal sources (e.g., online, friends/family) or from health care providers (HCPs). Sixty-three percent (n = 232) of women with decreased sexual desire did not seek help from informal sources, and only 18.68% sought help from HCPs. Across all sexual function domains, more women described seeking help from informal sources than from HCPs. The most commonly reported reason for not seeking help was belief that the experience was normal (e.g., reported by 41.87% with decreased arousal who did not seek help), followed by lack of time for appointments. Embarrassment and discomfort were also barriers to seeking care.Among women with decreased desire or arousal who sought help from an HCP, around half received no or unhelpful treatment (48.53% of women with low desire; 56.82% with low arousal). Among women with postpartum anorgasmia or pain who sought help from HCPs, most received helpful treatment (60% of women with anorgasmia, 56.76% with pain).No statistical differences were found in impact of childbirth on sexual function between women who did vs. did not seek help from informal sources for decreased desire, arousal, or orgasm. Women with sexual pain who did not seek help reported childbirth had a greater impact on sexual function (assessed by the SFQ-MIS) compared with women with pain who sought help (M = 3.87, SD=0.46 vs. M = 3.64, SD = 0.63; t(190) = 2.10, p = 0.019). Conclusions: A majority of women who experienced decreased sexual function postpartum in this study did not seek help. Many women who sought help from HCPs did not receive effective treatment, especially those with decreased desire or arousal. Although some women did not seek care because they believed decreased sexual functioning was normal or it did not bother them, other women reported patient-level barriers (e.g., embarrassment) to seeking help. This study reiterates the importance of routine assessment of sexual functioning in postpartum women and access to effective treatment. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Paid consultant or on a scientific advisory board: Astellas, Bayer, Daré, Duchesney, Field Trip, Lupin, Madorra, Materna, Mithra, Mitsubishi Tanaba NA, Ms. Medicine, Ovoca, Palatin Technologies, Pfizer, Sprout, Strategic Science Technologies (SST), TherapeuticsMD Institutional Grant Support (Clinical Trial Investigator): Dare/SST, Palatin Stock options: Viveve, Materna, Field Trip; Consultant to: Johnson & Johnson